Design and Development of a Website to Assess Students’ Good Deeds Using a Rule-Based Algorithm: A Case Study of Poncol State Vocational High School. - Krisna Nurhuda; Angga Prasetyo; Fauzan Masykur (MIKIR : Mathematics, Informatics, Knowledge And Information Research, 2026)
The recording of student behavior points at Poncol State Vocational High School still relies on paper forms and separate logbooks. This manual procedure leads to delays in data verification, the risk of miscalculations, and a lack of transparency. This website stores data on students’ positive behavior digitally and centrally. To process this data, the system uses a rule-based algorithm through if-then logic. Built using the Laravel framework and MySQL, this program includes features for student activity submissions, teacher verification, and point calculations. Functional testing was conducted using the Black Box method. The test results show that every feature on the admin, teacher, and student pages functions as originally designed. This system is capable of automatically determining eligibility for Field Work Practice (PKL) and grade promotion based on minimum point thresholds. This automated procedure replaces manual record-keeping on paper summary sheets.